Psychology of downshifting: substantive and causal aspects - Trukhan, Elena A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article discusses psychological, economic, political, philosophical and sociological approaches to studying the phenomenon of downshifting. Within the psychological approach, the substantive and causal aspects of downshifting are analyzed. Downshifting is viewed as a specific way of life, an alternative way to achieving success opposed to careerism, a psychological defense mechanism, a kind of escapism, a form of deviant behavior or a personality disorder, a manifestation of infantilization in adults. Psychological reasons for downshifting, such as role and value conflicts, middle age crisis, individual features of biorhythms, and professional burnout are defined.
Keywords: downshifting; social status; career; lifestyle; stress; burnout